A kinetic origami surfaces methodology - Osório, F. C.; Paio, A.; Oliveira, S. M. (Architectural Science Review, 2023)
This paper presents original research developed during PhD research. It proposes a multidisciplinary process as a methodology for the construction of thick, rigid origami surfaces to be used for kinetic architectural purposes. Origami surfaces that fold rigidly allow for strict geometry-based simulations that can reproduce rigorous rigid kinematics from the unfolded to the completely folded state, which is particularly important in large scale structures where motion must be predictable. The considered surfaces are regularly tessellated and have planar initial and final states. Through movement, these can assume a cycle of folding states with different three-dimensional configurations. The proposed method departs from concept, moves to geometry definition, kinematic simulation, structural evaluation, construction, and implementation for folding surfaces. It includes steps for evaluation and correction of issues as well as strategies for construction through digital fabrication with planar, thick materials. Its validity is demonstrated by its application in a constructed case study.